Caffeine and osteoporosis - Dworzański, Wojciech; Burdan, Franciszek; Potembska, Emilia; Tomaszewski, Marek; Tomaszewskia, Monika; Olchowik , Grażyna (Polish Journal of Public Health, 2010)
The incidence of osteoporosis and related fractures has increased dramatically in recent years all over the world and they have become one of the major health problems in Western countries. This growing tendency will probably continue, mainly due to the growing number of elderly people. Nowadays, certain steps are being made to find the risk factors in order to protect human health and decrease the costs related to this illness. Most of the patterns (70%) result from genetic factors. The correlation of genes and body mass index (BMI) with bone density is most often suggested. However, evidence concerning the correlation of lifestyle or age factors with the loss of bone mass is not as obvious. Many factors are being named, such as: lack of physical activity, sedentary work, low calcium consumption, smoking and high alcohol consumption as hazardous to elderly women. However, the influence of the effects of these factors on bone mineral density (BMD) in women after the menopause has not yet been completely defined. The influence of various caffeine dosages on the severity of osteoporosis is also disputable. The present work constitutes a review of the research into this problem.